2022
DOI: 10.3389/fcimb.2022.787209
|View full text |Cite
|
Sign up to set email alerts
|

Recently Evolved Francisella-Like Endosymbiont Outcompetes an Ancient and Evolutionarily Associated Coxiella-Like Endosymbiont in the Lone Star Tick (Amblyomma americanum) Linked to the Alpha-Gal Syndrome

Abstract: BackgroundTicks are hematophagous arthropods that transmit various bacterial, viral, and protozoan pathogens of public health significance. The lone star tick (Amblyomma americanum) is an aggressive human-biting tick that transmits bacterial and viral pathogens, and its bites are suspected of eliciting the alpha-gal syndrome, a newly emerged delayed hypersensitivity following consumption of red meat in the United States. While ongoing studies have attempted to investigate the contribution of different tick-inh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 78 publications
(126 reference statements)
1
8
0
Order By: Relevance
“…Francisella-like and Coxiella-like endosymbionts detected in our study are non-pathogenic mutualistic and/or commensal microbes, which play a key role in the tick's developmental process and pathogen transmission (Buysse et al 2021;Hussain et al 2022). In our study, about 97% of H. marginatum were infected by FLE, and only one tick was positive for CLE, which is coherent with previous observations that FLE outcompetes CLE in ixodid ticks (Kumar et al 2022). High prevalence of FLE in H. marginatum ticks was previously observed, as it seems to be an ancestral primary endosymbiotic organism (mandatory to tick survival), being involved in nutritional symbiotic interactions including folate and riboflavin biosynthesis pathways plus biotin biosynthesis that are crucial for tick metabolism (Buysse et al 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Francisella-like and Coxiella-like endosymbionts detected in our study are non-pathogenic mutualistic and/or commensal microbes, which play a key role in the tick's developmental process and pathogen transmission (Buysse et al 2021;Hussain et al 2022). In our study, about 97% of H. marginatum were infected by FLE, and only one tick was positive for CLE, which is coherent with previous observations that FLE outcompetes CLE in ixodid ticks (Kumar et al 2022). High prevalence of FLE in H. marginatum ticks was previously observed, as it seems to be an ancestral primary endosymbiotic organism (mandatory to tick survival), being involved in nutritional symbiotic interactions including folate and riboflavin biosynthesis pathways plus biotin biosynthesis that are crucial for tick metabolism (Buysse et al 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Another interesting aspect of tick bites causing AGS was the possible involvement of tick microbiomes including endosymbionts. A recent study proposed that an invasion of Francisella -like endosymbiont (FLE) replacing Coxiella-like endosymbiont (CLE) in A. americanum is associated with AGS 25 , although the genome sequences of the FLE, CLE, and another common endosymbiont, Rickettsia amblyommatis , do not contain bacterial alpha-1,3-galactosyltransferase gene in our search on the genome sequences. In addition to endosymbionts, other tick gut microbes may be involved, as a study in human gut microbiome found Enterobacteriaceae with alpha-1,3-galactosyltransferase genes.…”
Section: Discussionmentioning
confidence: 95%
“…Considering the bacteria genera with LinDA’s log 2 > 0.5 and BH adjusted P < 0.05, the Francisella genus was associated with the MCV group, suggesting that bacteria belonging to this genus should direct tick species toward transmitting less pathogens. This genus is composed of pathogenic species as well as endosymbionts that have been identified in many tick species ( 21 ). In particular, the latter which are detected in all life stages both in colony-reared and in field-collected ticks ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…This genus is composed of pathogenic species as well as endosymbionts that have been identified in many tick species ( 21 ). In particular, the latter which are detected in all life stages both in colony-reared and in field-collected ticks ( 21 ). High prevalence of Francisella was associated with decreased Rickettsia genus, which impairs tick borne pathogen transmission by outcompeting other bacterial genera ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%